KEBIJAKAN HUKUM PIDANA DALAM PENANGGULANGAN TERORISME DI INDONESIA - Tri Saputra, Agus (Universitas Tadulako, 2024)
Agus Tri Saputra D 102 18 039 criminal law policy in overcoming terrorism in Indonesia supervised by Benny Diktus Yusman and Hamdan Rampadio Formulating the problem of how to criminal law policy in overcoming criminal acts of terrorism in Indonesia. What are the obstacles and factors faced in overcoming criminal terrorism in Indonesia. Using normative juridical methods Referring to Seorjono Soekanto's typology, he explained that the study of approaches to normative law versus normative ones conceptualizes law as norms, rules, regulations and legislation that apply at a certain time and place as the product of a particular sovereign state power. The crime of terrorism is a form of cross-border crime that seriously threatens world order and peace. Terrorism is a crime that cannot be classified as an ordinary crime. Academically, terrorism is categorized as an